Kelompok Informasi Masyarakat Dan Masyarakat Informasi (Studi Kasus Kontribusi Kelompok Informasi Masyarakat Dalam Mewujudkan Masyarakat Informasi di Kota Magelang) - Ari Mukti; Rizza Arge Winanta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This paper aims to describe the contribution of Community Information Group in the development of the information society. The development of an information technology based service city, needs to be supported by community readiness. They are entities who have high information needs, able to apply information technology in various fields, and able to exchange digital data quickly over long distances. Currently, the Magelang City Government is committed to implementing a Smart City, supported by Magelang Cerdas Application, that makes it easier for the public to access local information and public services. However, community response is still low, so community information groups need support in encouraging the success of local government programs. The problem is studied descriptively qualitatively, by taking the location in Magelang City. Informants are officials of the Communication Informatics dan Statictics Agency and also management of Community Information Group who were chosen purposively. Research findings state that Community Information Group contributes in disseminating government programs to the community. However, the efforts made were less than optimal due to coordination factors, lack of human resources commpetence, priority issue, and budget issue.